Effect of Avian Corona Virus; A letter to Editor - Muhammad Hamza; Hamza Khalifa Ibrahim (ITScience (Information Technology and Science), 2022)
The poultry industry is the one of largest industries in Pakistan but unlucky it is facing a lot of problems. The purpose of this letter is to bring light to infectious Bronchitis and the method to control it. Infectious Bronchitis is a major disease in poultry It is a viral disease it spreads from bird to bird and it is a disease of the upper respiratory tract [1,2,3]. It is like the Human Coronavirus but Human Corona Virus was observed later in 2019 in Wuhan China [4,6] while avian coronavirus was observed many years ago. Infectious bronchitis is caused by Corona Virus which belongs to Corona Viridae. Corona viridae is very large group of viruses causing disease in human [5] as well as in birds. There are some major signs of infectious Bronchitis e.g plague in bronchioles, sneezing, coughing, and off feed. The main issue is that it is difficult to diagnose the disease without postmortem as some diseases have the same signs like gasping, sneezing and cough are also symptoms of Newcastle disease [7]. So for the confirmation of that disease postmortem is compulsory and we can also take help from the laboratory.